The construction of pad footing / Ahmad Danial Ahmad Tarmiji - Ahmad Tarmiji, Ahmad Danial (Universiti Teknologi MARA, Perak, 2018)
A foundation is that part of the structure that is in direct contact with the ground (Gopi,2010). Pad footing tend to be the simplest and cheapest foundation type and are used when the soil are relatively strong or when the column loads are relatively light (Seward,2006). The aim of this study is to explore reinforced concrete pad footing. The methods that are being used in the report are by observation, interview and document analysis. From the report, the construction method of reinforced concrete pad footing was discovered slightly the anti-thermite spraying on the concrete was not mention in theory plus the advantages and disadvantages of pad footing that was discovered was so many such as size of foundation, price, and size of building in construction. The conclusion is reinforced concrete pad footing is popular among the contractor to be used in the construction because of it price.